Internationalization and Globalization in Higher Education: An Insight on Effect of Machine Translators on Team Performance among Multicultural Students Working and Studying in Hungary - Koech, Daniel Kibet; Degago, Esayas; Kipkorir , Chris Simon Sitienei; Chittoo, Hemant Birandranath; Szabó, Attila Péter; Molnár, Edina (Journal of Ecohumanism, 2024)
Language barrier impedes team performance among employees working in a multilingual environment. Guided by the Technology Acceptance Model this study seeks; to determine the effect of machine translators on team efficiency, collaboration, trust building, and training among students on work-study jobs in Hungary. International students (N=105) from the University of Debrecen participated in the study. Findings indicate that machine translators significantly and positively contributed to team performance by boosting efficiency, collaboration, trust, and training. Every unit increase in use of Machine Translators translated to a corresponding increase in team efficiency, collaboration, trust, and training: a significant finding that indicates their instrumental role in breaking the language barrier in a linguistically diverse workplace. This study recommends the full adoption of machine translators to bridge the communication gap arising from language barriers in any multicultural environment consisting of multi-lingual team members